Image Processing: Machine Vision Applications 2008
DOI: 10.1117/12.764752
|View full text |Cite
|
Sign up to set email alerts
|

Video-rate or high-precision: a flexible range imaging camera

Abstract: A range imaging camera produces an output similar to a digital photograph, but every pixel in the image contains distance information as well as intensity. This is useful for measuring the shape, size and location of objects in a scene, hence is well suited to certain machine vision applications.Previously we demonstrated a heterodyne range imaging system operating in a relatively high resolution (512-by-512) pixels and high precision (0.4 mm best case) configuration, but with a slow measurement rate (one ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This approach is performed by gain modulating the image sensor during the integration time at the same frequency as the illumination modulation, thereby implementing a homodyne downconverter. This gain modulation can be achieved with the combination of a traditional image sensor and an external modulation device [1] but is more commonly achieved with a specialized complementary metal-oxide-semiconductor (CMOS) image sensor, with the modulation function designed into the pixels [2]- [4]. Objects that are close to the camera will exhibit a small phase shift in the returned light, which will basically be in phase with the sensor modulation, producing a bright pixel.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is performed by gain modulating the image sensor during the integration time at the same frequency as the illumination modulation, thereby implementing a homodyne downconverter. This gain modulation can be achieved with the combination of a traditional image sensor and an external modulation device [1] but is more commonly achieved with a specialized complementary metal-oxide-semiconductor (CMOS) image sensor, with the modulation function designed into the pixels [2]- [4]. Objects that are close to the camera will exhibit a small phase shift in the returned light, which will basically be in phase with the sensor modulation, producing a bright pixel.…”
Section: Introductionmentioning
confidence: 99%
“…Through careful selection of N and the length of the integration time, the heterodyne method minimizes the effects of harmonics better than is normally possible with a homodyne system. This enhances measurement accuracy [13].…”
Section: Heterodyne Modulationmentioning
confidence: 99%
“…Employing the 8 × 8 binning, the system could generate range images between 15.7 and 68.5 Hz with a best precision of 2.5 mm [15]. The penalty for this however, was significantly reduced spatial resolution.…”
Section: Revised Designmentioning
confidence: 99%
“…This provides the user with the ability to experiment with different configurations. The authors have found this to be invaluable for determining the frequencies that produce the best precision results [15,16]. It would be additionally useful if these frequencies could be changed "on the fly", in other words be configurable without requiring the downloading of new code.…”
mentioning
confidence: 99%
See 1 more Smart Citation